2006
DOI: 10.1158/0008-5472.can-06-0604
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation and Implications of Photodynamic Therapy Induction of Vascular Endothelial Growth Factor in Prostate Cancer

Abstract: Photodynamic therapy (PDT) is now an approved therapeutic modality,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 45 publications
4
80
0
Order By: Relevance
“…Hypoxia-induced stabilization of HIF (hypoxia inducible factor)-1a, followed by its binding to the HRE (hypoxia responsive element) in the VEGF promoter, is a major regulator of VEGF gene expression. 58 As our preliminary study indicates, VEGF expression has been used as an index of tumor tissue oxygenation, and the observed overexpression of VEGF after PDT was likely due to the hypoxia induced by photochemical reactions. 18 Jiang et al demonstrated that VEGF expression increased within the PDT-treated lesions and remained elevated for some weeks.…”
Section: Discussionmentioning
confidence: 91%
“…Hypoxia-induced stabilization of HIF (hypoxia inducible factor)-1a, followed by its binding to the HRE (hypoxia responsive element) in the VEGF promoter, is a major regulator of VEGF gene expression. 58 As our preliminary study indicates, VEGF expression has been used as an index of tumor tissue oxygenation, and the observed overexpression of VEGF after PDT was likely due to the hypoxia induced by photochemical reactions. 18 Jiang et al demonstrated that VEGF expression increased within the PDT-treated lesions and remained elevated for some weeks.…”
Section: Discussionmentioning
confidence: 91%
“…If p38 inhibition does not influence on photochemicallyinduced rupture of endosomes and lysosomes, inhibition of photochemical induced death signals, as the p38 activation, in PCI of genes is likely to increase the fraction of surviving transducable cells and may in this way increase the spesificity of the treatment. PDT induced p38 activation has by others also been associated with induction of VEGF using both BPD and Hypericin as photosensitizers (Hendrickx et al 2005, Solban et al 2006) and activation of p38 after hypericin PDT is in addition shown to upregulate cyclooxygenase-2 (Hendrickx et al 2003) and heme-oxygenase 1 (Kocanova et al 2007). Induction of both VEGF (Ferrara & Gerber 2001, Kowanetz & Ferrara 2006, COX-2 (Bakhle 2001) and heme-oxygenase (Jozkowicz et al 2007 Protein NuTu-19 WiDr A-431 p-EGFR decrease no effect no effect EGFR no effect no effect no effect p-ERK increase increase decrease ERK no effect no effect no effect p-JNK increase not detected not detected JNK no effect no effect no effect p-p38 increase increase increase P38 no effect no effect no effect Protein NuTu-19 A-431 p-EGFR decrease decrease EGFR decrease no effect p-ERK increase -ERK no effect -p-JNK --JNK no effect -p-p38 increase -P38 no effect - …”
Section: The Impact Of Mapk Signallingmentioning
confidence: 92%
“…The mechanism of tumor metastasis after PDT is not completely clear. At present, the common explanation to this is the up-regulation of angiogenic growth factor, such as VEGF following subcurative PDT (24)(25)(26). It has been well documented that PDT can induce severe hypoxia through over-consuming oxygen and damaging tumor vessel and blood flow (24), and that VEGF is up-regulated in hypoxia through transcription factors known as hypoxia-inducible factors (HIFs) that bind to the VEGF promoter (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that PDT can induce severe hypoxia through over-consuming oxygen and damaging tumor vessel and blood flow (24), and that VEGF is up-regulated in hypoxia through transcription factors known as hypoxia-inducible factors (HIFs) that bind to the VEGF promoter (32). Several kinds of antiangiogenic agents have been applied in treating tumorbearing animal in combination with PDT, and these combination therapies have achieved better therapeutic outcomes (24,25,31,33). Some previous reports have also shown that VEGF is up-regulated as early as in one day following PDT indicating that an increase in VEGF is an early event (24,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation